Caracterización de los estilos de aprendizaje en educación media en colegio privado y público de la ciudad de Ibagué (2020)
It is essential to state that learning styles allow us to identify the characteristics that students use to respond to different academic spaces, being notable to have high levels to respond to different conditions of the same. Therefore, it is possible to say that learning styles are goal-oriented techniques, with respect to the pedagogical efforts of middle education aimed at strengthening students' academic self-concept and the way they face difficulties schoolchildren in the educational institution. In Colombia there is evidence of the effect of the type of educational institution on student performance. In particular, students from private educational institutions perform better than those who attend public schools. The objective of this work was to establish the characterization of learning styles in 10th and 11th grade students from private and public schools in the city of Ibagué. In the account, a sample of 200 students was obtained, of which 100 belonged to grade 10 and 100 to grade 11. To achieve the comparison of learning styles, an empirical-analytical paradigm, quantitative approach, cross-sectional design and the applied instrument will be seen. CAMEA40 was used to collect the information. In the results found, it should be noted that, if there is significant evidence regarding the four learning styles evaluated, compared to CAMEA-40 in the students of a Public and a Private School. Likewise, the learning styles most used by the students will be determined: Pragmatic, Theoretical, and Reflective, for both tenth and one-time students, with better performance in students from private schools in La Ibagué city.